CORRELATION BETWEEN SOCIAL SUPPORT AND THE QUALITY OF LIFE ELDERLY IN PRAWIRODIRJAN SUB-DISTRICT YOGYAKARTA - Deodatus, Aditya J; Sigilipoe, Mitra A; Widagdo, The MM (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Background: The largest percentage elderly population in Indonesia in 2017 was in the province of Yogyakarta (13.81%). Increased life expectancy leads to changes in population, namely the higher percentage of elderly people. The increased number of elderly makes efforts to improve the quality of life of the elderly become important.Objective: To assess the correlation between social support and the quality of life of the elderly in the Prawirodirjan Sub-district, Gondomanan District, Yogyakarta Municipality.Methods: This is a cross-sectional study with a sample of 50 people. Measurement of social support was done using the MOS Social Support Survey questionnaire. Measurements for quality of life was done using the WHOQOL-BREF questionnaire. Data was analysed using Pearson correlation analysis.Results: Respondents were 50 people consisting of 10 men (20.0%) and 40 women (80.0%). Age of respondents ranged from 60-81 years. The statistical analysis results showed significant correlations between social support (MOS Social Support Survey) and quality of life (WHOQOL-BREF) in the Physical Health (r=0,771, p= 0,001), Psychological (r=0,550, p=0,001), Social Relationship (r= 0,664, p=0,001), Environment (r= 0,455, p = 0,001).Conclusion: There is a significant correlation between social support (MOS Social Support Survey) and quality of life (WHOQOL-BREF) in the elderly living in Prawirodirjan Sub-district, Gondomanan District, Yogyakarta Municipality.Â